THE EFFECT OF LEARNING MEDIA “AL ARABIYYAH BAINA YADAIK VOLUME ONE" ON ARABIC LEARNING OUTCOMES OF 8TH GRADE STUDENTS AT MTSN 1 DELI SERDANG - Lubis, Ahmad Taufiq; S, Fahrurrozi (Ihya al-Arabiyah: Jurnal Pendidikan Bahasa dan Sastra Arab, 2023)
This study specifically aims to examine the effect of Al-Arabiyyah Baina Yadaik learning media in the context of increasing Arabic language learning outcomes in class VIII students at MTsN 1 Deli Serdang. The phenomenon in the field shows that the dominance of conventional teaching methods that lack innovation and dependence on textbooks alone tend to create a passive learning environment, leading to a decrease in student motivation and learning outcomes. This condition emphasizes the imperative to adopt a more dynamic and technology-based learning approach, along with the demands of digital literacy in the contemporary era. By using a quantitative approach with an experimental design, this study validates the potential of Al-Arabiyyah Baina Yadaik as an interactive media designed for non-native learners, which holistically accommodates the development of four language skills (listening, speaking, reading, writing). The pilot test results showed strong evidence of a significant improvement in students' learning performance; the average score substantially increased from 64.5 to 97.5, followed by a drastic increase in the number of students who achieved the Minimum Completion Criteria (MCQ) from 7 to 18 individuals. In additional, field observations recorded a notable increase in the level of student activeness and enthusiasm in learning participation. The response from subject educators was also very positive, reflected in the percentage of media feasibility of 98% based on the evaluation of the aspects of appearance, material presentation, and benefits, all of which were categorized as “Very Feasible”. This finding firmly confirms the urgency of utilizing innovative and technology-adaptive learning media for optimizing the Arabic teaching and learning process which is not only effective, but also able to arouse students' intrinsic motivation and relevant to the dynamics of global education.